Pengabdian Kepada Masyarakat; Pemberdayaan Masyarakat Sadar Gizi Melalui Program GEBUK (Gerakan Atasi Gizi Buruk) - Zinnurain, Zinnurain; Mujiburrahman, Mujiburrahman (Fakultas Ilmu Pendidikan dan Psikologi, 2025)
The purpose of this community service activity is to implement Community Service; Empowering Nutrition-Conscious Communities through the